The grotesque between subjectivity and collectivity: revisiting the Venus of Willendorf project by Brenda Oelbaum - Mello, Júlia (Farol, 2023)
The article presents an analysis of the Venus of Willendorf project by Canadian artist Brenda Oelbaum, which began in 2008 and is still ongoing. Oelbaum rescues famous figures from the history of art, such as the Venus of Willendorf, constructing new languages of criticism of diets and body patterns. She talks about herself through photography, sculpture, video, performances and installations, mocking and calling on the public for collaborative actions through a poetic permeated by eccentricity and excess.